Pharmacokinetic/LDL‐C and exposure-response analysis of tafolecimab in Chinese hypercholesterolemia patients: Results from phase I, II, and III studies - Shuling Yan; Xia Zhao; Qiushi Xie; Weijuan Du; Qingyang Ma; Tongkang Zhu; Huan Deng; Lei Qian; Shirui Zheng; Yimin Cui (Wiley, 2023)
Abstract Tafolecimab, a novel fully human monoclonal antibody targeting PCSK9, has been assessed in Chinese healthy volunteers and patients with hypercholesterolemia. This analysis is to develop and qualify a population pharmacokinetics (PopPKs)/LDL‐C model to characterize tafolecimab PK and LDL‐C profiles, evaluate the impact of potential covariates on tafolecimab, estimate individual predicted exposure, and LDL‐C decreasing, furthermore, explore exposure-response relationship to support clinical use. Data from six clinical trials in China were used to develop the PopPK/LDL‐C model. A Michaelis-Menten approximation of the target‐mediated drug disposition (TMDD) model was used to describe PK data and indirect response (IDR) model was developed to estimate the LDL‐C profile. A stochastic approximation expectation maximization algorithm was applied to estimate PopPK/LDL‐C parameters. The PK/LDL‐C time course data for tafolecimab were well described by TMDD/IDR model. Baseline covariates resulting in statistically significant changes in PK/LDL‐C parameters included: body weight and sex on absorption rate constant; body weight, sex, and unbound PCSK9 on central volume; body weight and sex on clearance; baseline LDL‐C on first‐order rate constants for the removal of an effect); and disease and sex on maximum effect. However, the magnitudes of changes associated with these covariates do not necessitate dose adjustment. Exposure-efficacy relationship indicated that the nadir of LDL‐C reduction achieved with the steady‐state trough plasma concentration (Ctrough) of tafolecimab at 5 μg/mL, and no further LDL‐C decreasing with the increasing Ctrough. There was no exposure dependency observed in exposure‐safety exploration. The PopPK/LDL‐C model was successfully developed, validated, and predicted tafolecimab/LDL‐C concentrations and individual exposures.